PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN NASABAH MENYIMPAN DANA PADA BANK PEMERINTAH DI BANJARMASIN - Norrahmiati; Jumiati (Fekon Uvaya Banjarmasin, 2019)
The purpose of this study is to (1) know and analyse the influence of the service, marketing mix through product variables, pricing, promotion, place, people, physical evidence, and the process of costumer decisions to save funds at Government Banks in Banjarmasin, (2) know and analyse service marketing mix variables that have dominant influence on costumer decisions to save funds at Government Banks in Banjarmasin. This research is quantitative descriptive. The type of data used is qualitative and quantitative data, while the data source used are primary and secondary data. The population in this study are individuals or costumers who have connected to the Government Banks in Banjarmasin. The sampling technique used for this study was purposive sampling. The number of samples taken is 95 costumers. Technique for collecting data through observation, questionnaires , and documentation. Data analyse was performed using multiple regression methods. Based on the result of the analyse, the product, promotion, place of technical evidence, and process partially influence the costumers decision to save funda with the Government Banks in Banjarmasin. Whereas people have no effect on costumer’s decision to save funda with the Government Banks in Banjarmasin. Simultaneously product, pricing, promotion, place, people, physical to save funda with the Government Banks in Banjarmasin. Promotion is a variable that has dominant influence on customers decision to save funda with the Government Banks in Banjarmasin.